1997
DOI: 10.1177/004051759706700109
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Modeling Methodologies for Predicting the Strength of Air-Jet Spun Yarns

Abstract: The scope, usability, limitations and predictive power of four modeling methodologies are analyzed in this paper: mathematical models, empirical models, computer simulation models, and artificial neural network models. The predictive power of each of the four is estimated by comparing predicted yarn strength with experimentally obtained strengths for yarns spun using different process conditions and material parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 4 publications
0
29
0
Order By: Relevance
“…This computational model was trained to capture nonlinear relationship between input and output variables with scientific and mathematical basis. In recent days, commonly used model is layered feed-forward neural network with multi layer perceptions and back propagation learning algorithms (Vangheluwe et al, 1993, Rajamanickam et al, 1997, Zhu & Ethridge, 1997and Wen et al, 1998.…”
Section: Artificial Neural Network Modelmentioning
confidence: 99%
“…This computational model was trained to capture nonlinear relationship between input and output variables with scientific and mathematical basis. In recent days, commonly used model is layered feed-forward neural network with multi layer perceptions and back propagation learning algorithms (Vangheluwe et al, 1993, Rajamanickam et al, 1997, Zhu & Ethridge, 1997and Wen et al, 1998.…”
Section: Artificial Neural Network Modelmentioning
confidence: 99%
“…Rajamanickam et al [11], Guha et al [12] and Majumdar and Majumdar [13] have demonstrated that the prediction performance of ANN models is much better than that of classical mechanistic or regression models. Zhu and Ethridge [14] predicted the unevenness of spun yarns from advanced fiber information system (AFIS) parameters using ANN and obtained good prediction results.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu and Ethridge [21] used ANN models for predicting ring or rotor yarn hairiness. Yarn strength is predicted using different process conditions and material parameters in [6,19,20].…”
Section: Introductionmentioning
confidence: 99%